Calculation of Transmission Line Trip Probabilities under Forest Fire Condition - Hui LIU; Tao YANG; Jikeng LIN; Jingjing WANG; Bo YAN; Xiao LIU (Zhongguo dianli)
In recent years, line tripping incidents caused by forest fires occur frequently. How to accurately predict the line trip probability caused by forest fire has become one of the urgent issues that have attracted much attention. A new method for calculating transmission line trip probabilities is thus proposed in this paper using improved cellular automata forest fire spread model. Firstly some factors are introduced such as flame temperature, vegetation type, fire distance and precipitation, and the integrated impact of these factors on the line tripping is analyzed; then the improved cellular automata is used to predict the spread process of forest fires, and the accurate probability variation of line tripping caused by forest fire is thus obtained according to the spread situation. The effectiveness of the proposed method has been proved through case study, and it can provide a guide for the safe operation of power grid.